Implementasi Strategi Keuangan Dalam Novel “Home Sweet Loan” Karya Almira Bastari - Andre Wahyu Kusuma; Azis Nurdiansyah; Eva Dwi Kurniawan (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to analyze the financial strategies of four characters in the novel